Experimental Investigation of Energy Consumption for the Process of Initial Heating of a Substrate to the Fermentation Temperature - Zablodskiy М.M.; Spodoba M.O.; Spodoba О.O. (Problems of the Regional Energetics)
The aim of the work is to experimentally study the energy consumption for the process of initial heating of the substrate to the fermentation temperature in order to increase the energy efficiency of the biogas formation process. To achieve the goals set, a preparation and a series of exper-imental studies of the indicators of energy consumption for the process of initial heating of the substrate to the fermentation temperature were carried out. The working hypothesis is that the use of a heating cable built into the stirrer paddles reduces the energy costs for the process of initial heating of the substrate, increasing thus the energy efficiency of the biogas production. The most important result of the study was to obtain the dependences of the temperature change in the heating cable, substrate, reactor walls and energy consumption for heating and mixing dur-ing the initial heating of the substrate. The significance of the research results presented in the work lies in the fact that when using a heating cable built into the stirrer paddles, the process of initial heating of the substrate to the fermentation temperature occured faster on average by 16 minutes, and the amount of energy spent was also decreased on average by 6.6% for heating and 5.3% for mixing the substrate in a 40-liter biogas reactor. The implementation of the data obtained experimentally increased the energy efficiency of biogas production and the profitabil-ity of further processing of biogas into heat and electricity.